1998
DOI: 10.1016/s0954-6111(98)90343-2
|View full text |Cite
|
Sign up to set email alerts
|

An increase of soluble Fas, an inhibitor of apoptosis, associated with progression of COPD

Abstract: In chronic obstructive pulmonary disease (COPD) which consists of emphysema and chronic bronchitis, alveolar tissue and/or bronchiolar walls are progressively destroyed. This suggests cell death by necrosis and/or apoptosis although no direct evidence of apoptosis has been reported. It was speculated that the apoptosis-related factors are associated with the progression of COPD. Fas/Apo-1 receptor (Fas), Fas ligand (Fas-L) and soluble Fas ligand (sFas-L) are inducers, while soluble Fas (sFas) is an inhibitor o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
61
2
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(73 citation statements)
references
References 27 publications
9
61
2
1
Order By: Relevance
“…In these patients, the prevalence of nutritional depletion, a dietary intake significantly higher than estimated energy needs and evidence suggesting ongoing inflammatory reaction, as shown by the finding of higher serum IL-6 concentration, are in agreement with previously available data obtained in clinically stable COPD patients [1,[17][18][19][20]. Although no significant relationship could be established, these findings may indicate that the higher levels of IL-6 are not related to a deficit of energy intake and that other factors may contribute to the elevated levels of this cytokine in COPD patients.…”
Section: Discussionsupporting
confidence: 89%
“…In these patients, the prevalence of nutritional depletion, a dietary intake significantly higher than estimated energy needs and evidence suggesting ongoing inflammatory reaction, as shown by the finding of higher serum IL-6 concentration, are in agreement with previously available data obtained in clinically stable COPD patients [1,[17][18][19][20]. Although no significant relationship could be established, these findings may indicate that the higher levels of IL-6 are not related to a deficit of energy intake and that other factors may contribute to the elevated levels of this cytokine in COPD patients.…”
Section: Discussionsupporting
confidence: 89%
“…The univariable relation between elevated CRP level and COPD in the study data confirms previous studies reporting higher CRP-values in (known) COPD, 7,8,31,32 of which some considered high-sensitive CRP measurements (allowing for measurement of CRP level <3 mg/l). 7,31 Some of these studies compared COPD cases with their age-and sex-matched controls, 8,31 suggesting that the relationship was not caused by different age or sex distributions in COPD.…”
Section: Comparison With Existing Literaturesupporting
confidence: 88%
“…7,31 Some of these studies compared COPD cases with their age-and sex-matched controls, 8,31 suggesting that the relationship was not caused by different age or sex distributions in COPD. One study found that the higher CRP level in COPD was independent of smoking, and that CRP was lower in patients with COPD who used inhaled steroids.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Increases in the levels of the proapoptotic factor soluble Fas was reported in patients with chronic obstructive pulmonary disease (Yasuda et al, 1998). We found increases in apoptotic cells in the alveolar wall in elastasetreated mice at 5 days after injury.…”
Section: Discussionsupporting
confidence: 69%